Waste Management An Integrated Vision - Fernando Marmolejo Rebellon, Luis (IntechOpen, 2012)
Solid waste management generates big challenges for society due to its large variability in production and composition, and because of its sanitary and environmental impacts. To contribute in facing this situation, this book includes a worldwide overview of experiences and conceptual and technical developments attained through research and development projects. In addition to minimizing generation, considered as the most desirable practice, it includes alternatives of valuation for potentially recoverable waste and strategies to reduce final conditioning and disposition risks. The book includes contextual technical, economical, political and social aspects aimed at proposing integral solutions for the solid waste management.